Answers

The Brainliest Answer!
2014-09-13T23:00:54+05:30
Q.1)2√6-√5\3√5-2√6×3√5+2√6\3√5+2√6
=(2√6-√5)(3√5+2√6)\(3√5-2√6)(3√5+2√6)
=6√30+24-15-2√30\45-12
=4√30+9\33
Q.3)5+2√3\7+4√3=a+b√3
⇒5+2√3\7+4√3×7-4√3\7-4√3=a+b√3
⇒(5+2√3)(7-4√3)\(7+4√3)(7-4√3)=a+b√3
⇒35-20√3+14√3-18\49-48=a+b√3
⇒17-6√3=a+b√3
there fore by comparing a=17,b=-6
3 5 3
2014-09-14T07:10:37+05:30
 Q.1)2√6-√5\3√5-2√6×3√5+2√6\3√5+2√6
=(2√6-√5)(3√5+2√6)\(3√5-2√6)(3√5+2√6)
=6√30+24-15-2√30\45-12
=4√30+9\33
Q.3)5+2√3\7+4√3=a+b√3
⇒5+2√3\7+4√3×7-4√3\7-4√3=a+b√3
⇒(5+2√3)(7-4√3)\(7+4√3)(7-4√3)=a+b√3
⇒35-20√3+14√3-18\49-48=a+b√3
⇒17-6√3=a+b√3
there fore by comparing a=17,b=-6
0